Improving Students’ Grammar Mastery in Passive Voice by Using Jigsaw Method - Ance Jusmaya (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
This research is focused on developing   students' grammar mastery in passive voice   through jigsaw method. This is based on phenomenon that the development of communicative competence has become the main goal of language learning recently, then the role of grammar becomes very important in effective communication. The design of this research is quasi-experimental research that finds out the effect of Jigsaw method towards students grammar mastery. To determine the students’ grammar mastery, this study used a grammar test, through three pretests and a post-test. The pre-test was used to see the grammar mastery before treatment, and the post-test was used to see the difference in students' grammar scores after treatment. The research subjects were students from the Management Department at the University of West Sumatra who took Business English II. The data found that Jigsaw method had a significant effect on students' grammar mastery. This conclusion can be seen based on the analysis that found the average value of students in the pretest is calculated by 7 and student’s average score on post-test was 14. The observed t value is t = 3.88 and the standard significance is 0.05. Since t observed is greater than t table (T observed > t table), null hypothesis (Ho) is rejected and the alternative hypothesis accepted. So, based on these results, it is concluded that there is the statistical difference between pre-test in the 0.05 level. This means that teaching activities use jigsaw method has a significant influence on students' grammar mastery in learning passive voice